ANALISIS PENGGUNAAN APLIKASI KEUANGAN DI LEMBAGA KEUANGAN SMK NURUL ABROR AL ROBBANIYIN BANYUWANGI BERBASIS MANAJEMEN KEUANGAN SYARIAH - Lisah, Nora (KEADABAN: Jurnal Sosial dan Humaniora, 2023)
Abstract: Financial management in a company is part of the task of the company's leadership with the main responsibility in the form of important decisions regarding company investment and financing that must be carried out effectively and efficiently. Implementation of activities in the form of analysis of financial transactions with applications based on Islamic financial management at the financial institutions of SMK Nurul Abror Al Robbaniyin. Based on the results of interviews with the managers of these financial institutions, some of the obstacles they face include not managing computerized financial transactions so that they can build financial institutions that aim to provide the benefits of computer technology by speeding up the operational system for companies. With this, of course, it provides convenience, especially in storing data and providing satisfaction to the Institution's customers as well as with Islamic laws.